Organizational Citizenship Behavior Guru Sekolah Menengah Atas dan Sederajat di Lingkungan Pondok Pesantren - Niki Puspita Sari; Helmi Muhammad (UIN Raden Mas Said Surakarta, 2019)
The purpose of this study was to determine and analyze the influence of perceived organizational support, job satisfaction, and organizational commitment on Organizational Citizenship Behavior (OCB), and the role of organizational commitment in mediating influence between perceived organizational support and job satisfaction on OCB of teachers of Islamic boarding high schoolin Tulungagung. This study useda census method by distributing questionnaire to the entire population of 150 teachers. Data was analyzed using a partial least square approach. The results showed that the perceived organizational support does not significantly affect OCB,job satisfaction affects OCB, perceived organizational support affects organizational commitmet, job satisfaction affects organizational commitment, organizational commitment affects OCB, perceived organizational support affects OCB through organizational commitment, and job satisfaction affects OCB through organizational commitment.